Pelatihan Publikasi Ilmiah Guru-guru Kota Tangerang Selatan pada Jurnal Investigasi SMP Negeri 17 Vol. 4, No. 1, Maret 2023 - Gatot Kusjono; Suprianto Suprianto; Syamruddin Syamruddin (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2023)
Community service activities Training on Scientific Publications of South Tangerang City Teachers in the Investigation Journal Volume 4 No.1 SMP Negeri 17 aims to assist elementary and junior high school teachers in South Tangerang City in writing scientific manuscripts that will be published in ISSN journals. The training method is carried out using the method of mentoring, discussion, workshop and technical guidance (bimtek) writing scientific manuscripts in accordance with journal manuscript standards. The training results obtained as many as 8 elementary school teacher manuscripts (67%) and 4 junior high school teacher manuscripts (33%). The publication of teacher scientific manuscripts in the Journal Investigative Volume 4 Number 1 March 2023, is very helpful for teachers in improving the quality of scientific manuscript writing and is very helpful in raising groups.